Power BI and the datafication of Danish higher education. - Weinberg, Lindsay (Big Data & Society)
Power BI is a Microsoft data visualization and business intelligence platform currently being used for higher education governance at a range of institutions. This study contributes to critical scholarship on the normative dimensions and politics of data visualizations, with particular attention to how dashboards co-shape user subjectivities and are intertwined with educational policies that use time as a means of enacting higher education governance. Drawing on 11 interviews with administrative advisors and faculty connected to humanities programs that are particularly vulnerable to de-funding and enrollment challenges at a large public research university in Denmark, this paper investigates how the design, use, and marketing of Power BI are entangled with top-down higher education policy agendas. It emphasizes how students are constructed as discursive objects whose demographic information, academic progress, and workforce participation can be sorted, aggregated, and tracked in "real-time" for meeting performance metrics as well as regulatory compliance. However, this article also demonstrates how Power BI is a site where unanticipated frictions emerge. While the software is designed to render program administrators and faculty increasingly responsible for hedging against the vagaries of the post-graduation job market, in practice, participants report ambivalence and disengagement, navigate issues of transparency and accuracy, and attempt to leverage the platform to creatively resist threats to program defunding.